Cabergoline as a preventive migraine treatment: A randomized clinical pilot trial. - Astrid Johannesson Hjelholt; Flemming Winther Bach; Helge Kasch; Henrik Støvring; Troels Staehelin Jensen; Jens Otto Lunde Jørgensen (PLoS ONE)
Background Beneficial effects of dopamine agonist treatment on migraine have been reported but remain to be properly tested. The aim of this study was to examine the effect of cabergoline as preventive treatment for migraine. Methods In a double-blind, placebo-controlled pilot study, 36 adults with ≥  6 monthly migraine days were enrolled at Aarhus University Hospital. Following a 28-days baseline period, participants were randomized to receive cabergoline 0.5 mg or placebo once weekly for 12 weeks as add-on treatment. An electronic headache diary was completed daily, and headache questionnaires and blood tests were collected at baseline and following the treatment period. Primary outcome was change in monthly migraine days. The trial was registered with ClinicalTrials.gov (NCT05525611). Results Of 101 assessed participants, 36 were enrolled. Baseline monthly migraine days were 13.6 (4.1) in the cabergoline group and 14.0 (5.3) in the placebo group. No significant overall difference in the reduction of monthly migraine days was observed. However, among participants with episodic migraine (n = 20), the mean (SE) reduction in monthly migraine days from baseline to the last 28 days of the treatment period was -5.4 (1.3) with cabergoline compared to -1.8 (0.9) with placebo (p = 0.04) [odds ratio: 0.79 (95% CI 0.65 - 0.95), p = 0.014]. In participants with chronic migraine (n = 13), the reduction in monthly migraine days was not significantly different in the two groups. Patients' global impression of change significantly improved after cabergoline treatment as compared to placebo in the entire group of participants (p = 0.006). The number of participants with episodic migraine achieving ≥  50% reduction in monthly migraine days tended to increase after cabergoline (p = 0.07). Adverse effects were reported by seven participants on cabergoline and four on placebo, none of which were serious. Conclusion Cabergoline significantly reduced monthly migraine days in episodic migraine without serious adverse effects, supporting further investigation into the use of cabergoline for migraine prevention.